Hepatitis C viraemia reversibly maintains subset of antigen‐specific T‐bet+ tissue‐like memory B cells - Chang, L.‐Y.; Li, Y.; Kaplan, D. E. (Journal of viral hepatitis, 2017)
Summary Background: Chronic antigen exposure and/or ageing increases the frequency of T‐box expressed in T cells (T‐bet)‐expressing B‐lymphocytes in mice. The frequency and significance of B‐cell T‐bet expression during chronic hepatitis C (HCV) infection in human subjects has never been described. Methods: Healthy controls, cirrhotic and noncirrhotic HCV‐infected patients, and non‐HCV patients with cirrhosis were recruited. Peripheral blood mononuclear cells were phenotyped for expression of T‐bet and related markers by flow cytometry. In a subset of patients who underwent antiviral therapy and were cured of HCV infection (sustained virological response), the dynamics of T‐bet expression in B cells was monitored. After cure, convalescent B cells were tested for T‐bet expression after re‐exposure to infected plasma or recombinant HCV proteins. Results: Forty‐nine patients including 11 healthy donors, 30 hepatitis C‐infected individuals (nine with liver cancer, 13 with cirrhosis, eight without cirrhosis) and eight patients with cirrhosis due to non‐HCV‐related cause were recruited. We found that B cells in patients with chronic HCV exhibited increased frequency of T‐bet+ B cells relative to noninfected individuals (median 11.5% v. 2.2%, P<.0001) but that there were no significant differences between noncirrhotic, cirrhotic and cancer‐bearing infected individuals. T‐Bet+ B cells expressed higher levels of CD95, CXCR3, CD11c, CD267 and FcRL5 compared to T‐bet− B cells and predominantly exhibit a tissue‐like memory CD27−CD21− phenotype independent of HCV infection. T‐bet+ B cells in HCV‐infected patients were more frequently class‐switched IgD−IgG+ (40.4% vs. 26.4%, P=.012). Resolution of HCV infection with direct‐acting antiviral (DAA) therapy leads to a marked reduction in the frequency of T‐bet+ B cells (median 14.1% pretreatment v. 6.7% end of treatment v. 6.1% SVR12, P≤.01). Re‐exposure of convalescent (cured) B cells to viremic plasma and recombinant HCV E2 protein led to re‐expression of T‐bet. Conclusion: Chronic antigenemia in chronic HCV infection induces and maintains an antigen‐specific T‐bet+ B cell. These B cells share markers with tissue‐like memory B cells. Antigen‐driven T‐bet expression may be a critical suppressor of B‐cell activation in chronic HCV infection.